Pengaruh kinerja keuangan, kinerja lingkungan dan ukuran perusahaan terhadap nilai perusahaan dengan pengungkapan lingkungan sebagai variabel intervening - Suyanto, Elvira; Wibisono, Chablullah; Robin, Robin; Satriawan, Bambang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of financial performance, environmental performance and company size on firm value with environmental disclosure as an intervening variable in basic and chemical industry sector companies listed on the Indonesia Stock Exchange (IDX). This research was conducted using quantitative methods. The processed data of this study were determined by setting criteria. The amount of data that meets is 70 data and will be tested with panel regression testing. The results of this study explain that for environmental performance variables and firm size have a significant positive effect on firm value. Financial performance variables and environmental disclosure have an insignificant effect on firm value. The firm size variable has a significant positive effect on environmental disclosure. The financial performance variable has a significant negative effect on environmental disclosure and the environmental performance variable has an insignificant effect on environmental disclosure. Financial performance variables, environmental performance and company size have an insignificant effect on firm value through environmental disclosure as mediation.